Subcellular localization of acetyl-CoA carboxylase in the apicomplexan parasite Toxoplasma gondii - Jelenska, J. (The National Academy of Sciences, 2001)
Apicomplexan parasites such as Toxoplasma gondii contain a primitive plastid, the apicoplast, whose genome consists of a 35-kb circular DNA related to the plastid DNA of plants. Plants synthesize fatty acids in their plastids. The first committed step in fatty acid synthesis is catalyzed by acetyl-CoA carboxylase (ACC). This enzyme is encoded in the nucleus, synthesized in the cytosol, and transported into the plastid. In the present work, two genes encoding ACC from T. gondii were cloned and the gene structure was determined. Both ORFs encode multidomain proteins, each with an N-terminal extension, compared with the cytosolic ACCs from plants. The N-terminal extension of one isozyme, ACC1, was shown to target green fluorescent protein to the apicoplast of T. gondii. In addition, the apicoplast contains a biotinylated protein, consistent with the assertion that ACC1 is localized there. The second ACC in T. gondii appears to be cytosolic. T. gondii mitochondria also contain a biotinylated protein, probably pyruvate carboxylase. These results confirm the essential nature of the apicoplast and explain the inhibition of parasite growth in cultured cells by herbicides targeting ACC.